(untitled) (Journal of Medical & Health Sciences Review, 2025)
Introduction: The purpose of this study was to compare the functional outcome between the first and second knee replacement in patients who underwent staged bilateral total knee arthroplasty. Methods: 40 patients who had staged bilateral knee replacements were identified and post operatively followed for one, three and twelve months. Data on pain scores, walking ability, use of walking aids, range of movement, instability, muscle strength, and length of hospital stay (LOS) were recorded. The difference in data between the first and second knee was assessed. Results: Between the first and second procedure, groups maintained their statistical comparability. There was a significant difference between the first and second knee in three results. In terms of postoperative walking ability, the second knee’s mean score was 4.67, while the first knee’s was 3.26 (p=0.029). The mean score for the need for a walking aid following surgery was 4.93 for the second knee and 5.48 for the first (p=0.01). Second knee mean LOS was 4.19 days, while first knee mean LOS was 5.92 days (p=0.05). Every other comparison of data was not statistically significant. Conclusion: After second knee replacement, patients have a decreased LOS and continue to improve with regards to walking ability and use of walking aids.